2013
DOI: 10.4071/imaps.379
|View full text |Cite
|
Sign up to set email alerts
|

40 μm Ag/Au Flip-Chip Joints by Solid-State Bonding at 200°C

Abstract: AbstractÀIn this research, 40 mm silver/gold (Ag/Au) composite flip-chip interconnect joints between silicon (Si) chips and copper (Cu) substrates were demonstrated. The bonding was achieved by a solid-state process at a low temperature of 2008C for 5 min with the pressure applied at 250À400 psi (1.7À2.7 MPa), corresponding to 0.22À0.35 g of force per joint. To begin with, an array of 50 3 50 30 mm Ag/10 mm Au columns with 40 mm in diameter and 100 mm in pitch was fabricated by photolithographic and electropla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Cu commonly used for CMOS and Au commonly used in MEMS can be solid-state bonded together without additional material. A study has demonstrated for Cu-Au bonding at 200 °C for 5 min where Au was deposited onto columns to prevent oxidation of Cu[54]. However, the Cu bonding interface (unprotected surface) must be cleaned before bonding to remove copper oxides which will cause the bonding to fail.2.2.8 Cu-Sn Solid-State BondingCu-Sn solid-state bonding was performed in studies achieving lowbonding temperature from 150 to 200 °C [55] [56].…”
mentioning
confidence: 99%
“…Cu commonly used for CMOS and Au commonly used in MEMS can be solid-state bonded together without additional material. A study has demonstrated for Cu-Au bonding at 200 °C for 5 min where Au was deposited onto columns to prevent oxidation of Cu[54]. However, the Cu bonding interface (unprotected surface) must be cleaned before bonding to remove copper oxides which will cause the bonding to fail.2.2.8 Cu-Sn Solid-State BondingCu-Sn solid-state bonding was performed in studies achieving lowbonding temperature from 150 to 200 °C [55] [56].…”
mentioning
confidence: 99%